2007
DOI: 10.2486/indhealth.45.289
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Work Practices on Personal Exposure to Glutaraldehyde among Health Care Workers

Abstract: Glutaraldehyde is a potential sensitizer and has been implicated in the literature as a cause of respiratory irritation and asthma among health care workers. In order to evaluate the effect of work practices and general ventilation system on employees' peak exposure to glutaraldehyde, 42 breathing zone personal air samples were taken in five hospitals. In addition, work practices were observed and recorded during the course of sampling and were classified into three categories. Presence of local or general ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 17 publications
4
29
1
1
Order By: Relevance
“…The excellent properties of glutaraldehyde makes it the first choice in health centres in terms of considerations for health and safety in the workplace. Many papers illustrated and described the hazards of glutaraldehyde to the exposed health workers in the hospital environment [17,18]. However there is very little evidence in the primary care setting even though it is more utilized by the population.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The excellent properties of glutaraldehyde makes it the first choice in health centres in terms of considerations for health and safety in the workplace. Many papers illustrated and described the hazards of glutaraldehyde to the exposed health workers in the hospital environment [17,18]. However there is very little evidence in the primary care setting even though it is more utilized by the population.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that contribute to exposure of glutaraldehyde are inadequate and unsafe working practices [17], insufficient ventilation [18], and the failure to use goggles, protective clothing and gloves [19]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reported adverse health effects related to short term exposure to glutaraldehyde are due to its irritant effect (Cohen and Patton, 2006). They include irritation to the nose, eye and pharynx leading to sore throat, sneezing, cough, headache, nausea, rash and redness of skin (Takigawa and Endo, 2006;Nayebzadeh, 2007). Moreover, a sensitizing effect may occur due to long term exposure to glutaraldehyde (Waters et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…work practices have a significant effect on reducing GA exposure level and its adverse health effects (Nayebzadeh, 2007). Health studies of workers exposed to glutaraldehyde have shown that good work practices prevent allergic skin reactions (OSHA, 2006) and considered as a primary prevention to reduce occupational asthma (Heederik et al, 2012).…”
Section: Introductionmentioning
confidence: 99%